E-Governance in Paracale: A Digital Transformation for Improved Public Service Delivery and Citizen Engagement - Dela Peña, Marlo (JPAIR Multidisciplinary Research, 2025)
This study examines the e-government services in the Local Government Unit (LGU) of Paracale, Philippines, examining the impact of digital transformation on public service delivery and citizen engagement. The research aims to assess the functionality, reliability, usability, performance efficiency, compatibility, maintainability, portability, and security of the e-governance platform using the ISO 25010:2011 standard. Employing a quantitative approach, a survey questionnaire utilizing a five-point Likert scale was administered to twenty-four LGU employees with direct experience on e-governance platform to evaluate the system's performance across various dimensions. The findings reveal that the e-governance system in Paracale is highly effective, demonstrating robust functionality, reliable performance, user-friendly interfaces, and strong security measures. The platform has significantly enhanced public service delivery, promoted transparency, and fostered citizen engagement. The study identified specific areas for improvement, such as optimizing response times and enhancing the software's reusability. The study concludes that the e-governance system in Paracale provides a valuable model for other local government units seeking to embrace digital transformation. The research underscores the importance of investing in robust e-governance systems that are user-centric, secure, and adaptable to evolving needs, ultimately contributing to more efficient, transparent, and responsive governance.
Keywords: Social Science; public administration; e-governance; local government unit; quantitative research; Philippines